2016
DOI: 10.1088/0953-8984/28/40/403002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ordering of block copolymer thin films

Abstract: Block-copolymers self-assemble into diverse morphologies, where nanoscale order can be finely tuned via block architecture and processing conditions. However, the ultimate usage of these materials in real-world applications may be hampered by the extremely long thermal annealing times-hours or days-required to achieve good order. Here, we provide an overview of the fundamentals of block-copolymer self-assembly kinetics, and review the techniques that have been demonstrated to influence, and enhance, these orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 615 publications
4
156
0
1
Order By: Relevance
“…1). We spin-cast and anneal polystyrene- block -poly(methyl methacrylate) diblock copolymers (PS- b -PMMA) to yield ordered nanoscale phases5181920, and selectively infiltrate the PMMA block with alumina using a vapour-phase precursor (trimethylaluminium)2122. This selective infiltration synthesis (SIS) serves two roles: the infiltration ‘fixes' the BCP film, rendering it insoluble and allowing additional polymer film applications atop; and preferential loading of the PMMA block with alumina swells this phase, generating subtle surface topography coincident with the morphology (1–4 nm; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We spin-cast and anneal polystyrene- block -poly(methyl methacrylate) diblock copolymers (PS- b -PMMA) to yield ordered nanoscale phases5181920, and selectively infiltrate the PMMA block with alumina using a vapour-phase precursor (trimethylaluminium)2122. This selective infiltration synthesis (SIS) serves two roles: the infiltration ‘fixes' the BCP film, rendering it insoluble and allowing additional polymer film applications atop; and preferential loading of the PMMA block with alumina swells this phase, generating subtle surface topography coincident with the morphology (1–4 nm; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The materials presented herein should immediately be useful for a wide variety of nano-materials applications. Where lower defectivity is necessary, the presented assembly strategy could easily be combined with established directed self-assembly methods, which can rapidly generate aligned BCP phases with considerably lower defectivity20. An exciting avenue for future investigation is to study the interplay between directed self-assembly methods and the responsive layering described herein.…”
Section: Resultsmentioning
confidence: 99%
“…with n A,B the number of moles of polymers A and B, respectively, and φ A,B their volume fractions. The Flory–Huggins parameter can be split up into an entropic component χ S and an enthalpic component χ H …”
Section: Energy Minimization During Bcp Microphase Separation At the mentioning
confidence: 99%
“…However, the most widely used method to fabricate these nanopatterns, photolithography, is inherently limited in terms of the achievable feature size, and its advanced counterpart, extreme ultraviolet photolithography, is dauntingly costly and mostly inaccessible to the typical scientist. In this light, block copolymer (BCP) self‐assembly serves as an attractive alternative as it enables access to sub‐10 nm and supra‐100 nm nanopatterns in an incredibly simple manner (e.g., heating in an oven) . BCPs are highly available and affordable working tools for any scientist because they can be easily synthesized in the lab via various controlled/living polymerization techniques including atom transfer radical polymerization (ATRP), single‐electron transfer living radical polymerization, reversible addition–fragmentation chain transfer polymerization, nitroxide‐mediated polymerization, ionic polymerization, and ring‐opening metathesis polymerization …”
Section: Introductionmentioning
confidence: 99%
“…In this review, we discuss recent approaches, primarily those reported within the past 10 years, to achieving perpendicular microdomains via thermal annealing to provide the readers with a toolbox to work with. Solvent vapor annealing techniques will not be discussed because their notorious sensitivity to operating conditions and resultant non‐equilibrium, trapped BCP structures/orientation may not be readily applicable . Lateral order will only be touched on qualitatively since an in‐depth analysis for every method is deemed excessive to the scope of this review.…”
Section: Introductionmentioning
confidence: 99%